What does the COVID-19 pandemic teach us about global value chains? The case of medical supplies - Gereffi, Gary (J Int Bus Policy, 2020)
The COVID-19 pandemic has caused a dramatic shortage in the medical supplies needed to treat the virus due to a massive surge in demand as the disease circled the globe during the first half of 2020. Prior to the crisis, there was an interdependence of trade and production for medical supplies, with advanced industrial countries like the United States and Germany specializing in the relatively high-tech medical devices sector, while low-cost production hubs such as China and Malaysia were leading producers of less technologically sophisticated personal protective equipment (PPE) products such as face masks, surgical gloves, and medical gowns. After the COVID-19 outbreak, global shortages of PPE products emerged as many affected countries imposed export controls and sought ways to boost domestic output. A case study of the face mask value chain in the United States shows misalignments between the priorities of U.S. federal government officials and the strategies of leading U.S. multinational producers of face masks, which resulted in exceptionally costly policy delays in terms of health outcomes. On balance, the U.S. shortage of N95 respirators during the COVID-19 pandemic is more a policy failure than a market failure. The global value chain framework highlights strategic options that could lead to more resilient supply chains and diversified sourcing patterns.